2012
DOI: 10.1386/jaah.2.3.289_7
|View full text |Cite
|
Sign up to set email alerts
|

A Place for opportunity: The Block, representing the Council Estate in a youth theatre setting

Abstract: This article explores issues surrounding the representation of contested place by looking at the links between the Council Estate and social well-being in a specific project. The National Youth Theatre's The Block, was a new writing piece premiered as part of their 'Playing Up II' programme. Playing Up II attempted to offer access to higher education in the performing arts to those not in education, employment or training (NEETS). The article focuses on the play's portrayal of the problematic Council Estate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Previous research highlights the correlation between learning and well-being, satisfaction, optimism and efficacy (Feinstein and Hammond 2004;Feinstein et al 2008). Additionally, participants felt they were providing a learning experience for others through challenging perceptions with their acts, which aligns with previous research findings regarding the ability of theatre and performance-based work to appreciate the experiences of individuals (Low 2010), and enhance representation and aspiration (Beswick 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous research highlights the correlation between learning and well-being, satisfaction, optimism and efficacy (Feinstein and Hammond 2004;Feinstein et al 2008). Additionally, participants felt they were providing a learning experience for others through challenging perceptions with their acts, which aligns with previous research findings regarding the ability of theatre and performance-based work to appreciate the experiences of individuals (Low 2010), and enhance representation and aspiration (Beswick 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Torrissen (2015) suggested that collaborative theatre projects provide radically different solutions to the health problems encountered by individuals than those offered by the biomedical model of health, since they focus on resources, personhood, enablement, social support and empowerment to promote health and well-being, rather than on treatment and diagnosis. Beswick (2012) reports on the role that a National Youth Theatre educational outreach initiative played in the opportunity structures for young people, in addition to issues of representation and aspiration. However, performance also has particular associated challenges and has been recognized as a potentially stress-inducing activity.…”
Section: Introductionmentioning
confidence: 99%
“…38 This exchange echoes the popular belief that there is a correlative relationship between the council estate environment and the supposed 'pathological' behaviour of estate residents. 39 The characters' cycles of crimi nal, ostensibly immoral behaviour (spiralling into debt due to unwise spending habits, involvement in crime, misogyny, violence), are behaviours often associated with estate residents. The exchange between David and the gang, and the above exchange between David and Kojo, take place on the basketball court of the estate.…”
Section: Representing Crime On the Council Estatementioning
confidence: 99%